The Role of Kisspeptin in the Control of the Hypothalamic-Pituitary-Gonadal Axis and Reproduction - Xie, Qinying; Kang, Yafei; Zhang, Chenlu; Xie, Ye; Wang, Chuxiong; Liu, Jiang; Yu, Caiqian; Zhao, Hu; Huang, Donghui (Frontiers in Endocrinology, 2022)
The discovery of kisspeptin as key central regulator of GnRH secretion has given people a new understanding of the neuroendocrine regulation of human reproduction. Kisspeptin activates the signaling pathway by binding to its receptor kisspeptin receptor (KISS1R) to promote GnRH secretion, thereby regulating the hypothalamic-pituitary-gonadal axis (HPG) axis. Recent studies have shown that kisspeptin neurons located in arcuate nucleus (ARC) co-express neurokinin B (NKB) and dynorphin (Dyn). Such neurons are called KNDy neurons. KNDy neurons participate in the positive and negative feedback of estrogen to GnRH secretion. In addition, kisspeptin is a key factor in the onset of puberty, and also regulates the processes of female follicle development, oocyte maturation, and ovulation through the HPG axis. In male reproduction, kisspeptin also plays an important role, getting involved in the control of Leydig cells, germ cells progression and sperm functions. Mutations in the KISS1 gene or disorders of the kisspeptin/KISS1R system may lead to clinical symptoms such as idiopathic hypogonadotropic hypogonadism (iHH), central precocious puberty and female infertility. Understanding the role of kisspeptin in the reproductive axis and related mechanisms will help the future application of kisspeptin in disease diagnosis and treatment. In this review, we critically appraise the role of kisspeptin in the HPG axis, including its signaling pathways, negative and positive feedback mechanisms, and its control on female and male reproduction.